2020
DOI: 10.1093/neuros/nyaa148
|View full text |Cite
|
Sign up to set email alerts
|

Diabetes Insipidus After Endoscopic Transsphenoidal Surgery

Abstract: BACKGROUND Diabetes insipidus (DI) is a recognized transient or permanent complication following transsphenoidal surgery (TSS) for pituitary tumors. OBJECTIVE To describe significant experience with the incidence of DI after TSS, identifying predictive characteristics and describing our diagnosis and management of postoperative DI. METHODS A retrospective ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(33 citation statements)
references
References 28 publications
2
29
2
Order By: Relevance
“…The results are comparable to other studies that reported CSF leak rates of less than 10% ( 40 , 41 ). A higher body mass index (BMI) and perioperative hydrocephalus may have an impact on the occurrence of CSF leakage ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…The results are comparable to other studies that reported CSF leak rates of less than 10% ( 40 , 41 ). A higher body mass index (BMI) and perioperative hydrocephalus may have an impact on the occurrence of CSF leakage ( 42 ).…”
Section: Discussionmentioning
confidence: 99%
“…External validations are necessary to assess the capability to generalize a prediction model on other similar populations (34). Although several predictive models were proposed in the literature to stratify patients following sellar surgery, external validations were not performed (3,(7)(8)(9)(30)(31)(32). In the present study, a second cohort from 2020-2021 was used to externally validate the potential predictors identified from multivariate analysis performed in the 2016-2019 cohort.…”
Section: Discussionmentioning
confidence: 99%
“…The degree of damage correlates with the severity of vasopressin deficits and produces a spectrum of water and electrolyte imbalance ( 6 ). Although the incidence rate of permanent DI has decreased in modern practice, transient postoperative DI remains common ( 2 , 7 , 8 ). In some patients, the duration of transient postoperative DI can last for weeks to months and necessitate desmopressin replacement ( 5 , 7 ).…”
Section: Introductionmentioning
confidence: 99%
“…We recently reported an overall rate of DI after transsphenoidal surgery of 14.7% and a rate of permanent DI of 4.6%. 7 Postoperative CSF leak after transsphenoidal surgery can occasionally be treated conservatively with lumbar drainage, but it often requires reoperation for repair of the skull base defect. 17,38 Previously identified predictors of CSF leak post-transsphenoidal surgery include body mass index, identification of intraoperative leak, and pre- operative hydrocephalus, with rates ranging from 2.6% to 11%.…”
Section: Discussionmentioning
confidence: 99%
“…Patients require careful monitoring for these problems, and institutional protocols in the perioperative period can help limit their occurrence. 6,7 Many of these patients also require longterm follow-up for management of endocrinological and neurosurgical issues, but few studies have discussed the optimum strategy for postoperative management in this patient population. 15 We aimed to describe the experience of our institution in the pre-, intra-, and postoperative management of a broad range of patients with sellar pathology who undergo transsphenoidal surgery.…”
mentioning
confidence: 99%